Influence of Humidity and Greenhouse Microclimate on the Efficacy of Beauveria bassiana (Balsamo) for Control of Greenhouse Arthropod Pests. Issue 5 (24th October 2014) - Shipp, J. L.; Zhang, Y.; Hunt, D. W. A.; Ferguson, G.
Abstract : This study investigated the influence of different humidity levels on percentage of infection by Beauveria bassiana (Balsamo) Vuillemin (Hyphomycetes) (Botanigard Emulsifiable Suspension formulation) on greenhouse insect and mite pests, and their commercially available biological control agents. The target insect and mite species were sprayed with B. bassiana and evaluated in petri dish trials under controlled environment conditions, on cucumber leaves under greenhouse crop conditions, and under fully sprayed greenhouse conditions. Results of this study showed that in petri dish trials, a humidity of 97.5% RH resulted in significantly higher percentage of infection (60–88.8%), while at 75 and 80% RH only 15.3–43.9% of the pest insects were infected. On leaf surfaces, the differences in ambient humidity did not cause as great of variations in percentage of infection as in the petri dish trials. Increasing greenhouse humidity by 15% RH caused an increase of 17–25% in percentage of infection. Under high humidity conditions, whole greenhouse sprays with B. bassiana successfully suppressed populations of Frankliniella occidentalis (Pergande) and Trialeurodes vaporariorum (Westwood). Tetranychus urticae Koch was not infected by B. bassiana at significant levels in any of the trials. Predatory mites can be used with B. bassiana, while adult Orius insidiosus (Say), Aphidius colemani Viereck, and Dacnusa sibirica Telenga are not recommended to be introduced during the application of B. bassiana . Encarsia formosa Gahan, Eretmocerus eremicus (Rose and Zolnerowich), and Aphidoletes aphidimyza (Rondani) need to be used with caution when B. bassiana is applied.